Kamila Janiak i punk - Świeściak, Alina (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The author presents poetry by Kamila Janiak in the context of avant-guard pop-culture. She deals mainly with punk and cyber-punk motifs of this poetry, which alow to understand them as a feminist, post-human and anty-capitalist project. She shows how Janiak for her purposes uses d.tournements: she takes on the one hand principles, which rule in the “controlled societies” and on the other hand pop-culture aesthetics and psychodelic rock music.